Hydro-sedimentological computational tool: case study of the Mogi-Guaçu SHP (Brazil-SP) - Miranda, Renato Billia de; Guimarães, Tainá Thomassim; Martinez, Carlos Eduardo Nunes Medina; Bielenki Júnior, Cláudio; Mauad, Frederico Fabio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The hydro-sedimentological studies are complex and of great importance, mostly in countries with large amounts of water resources and with its energy matrix predominantly hydraulic. The assessment of the amount of sediment carried through water bodies is more difficult mainly due to the amount of involved quantities, which require the adoption of probabilistic or deterministic estimation methods. In this context, this paper presents a case study that applies the hydros-sedimentological module from the computational tool NH Statistic and Sediment, developed by one of the authors, written in Visual Basic for Applications to determine total sediment discharge using data from the Mogi-Guaçu Small Hydro Electric Power Plant (SP-Brazil). Among the surveys, the reduction of total sediment discharge was verified, which was expected. Likewise, the results provided by the developed computational tool were compared to the results of other softwares showing minimal differences, giving validity and consistency to the applied method. It’s worth mentioning that the method used in this case study may be replicated in other places, giving more information to assist the water resource management.